Expression of Tau Pathology-Related Proteins in Different Brain Regions: A Molecular Basis of Tau Pathogenesis - Hu, Wen; Wu, Feng; Zhang, Yanchong; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (Frontiers in Aging Neuroscience, 2017)
Microtubule-associated protein tau is hyperphosphorylated and aggregated in affected neurons in Alzheimer disease (AD) brains. The tau pathology starts from the entorhinal cortex, spreads to the hippocampus and frontal and temporal cortices, and finally to all isocortex areas, but the cerebellum is spared from tau lesions. The molecular basis of differential vulnerability of different brain regions to tau pathology is not understood. In the present study, we analyzed brain regional expressions of tau and tau pathology-related proteins. We found that tau was hyperphosphorylated at multiple sites in the frontal cortex, but not in the cerebellum, from AD brain. The level of tau expression in the cerebellum was about 1/4 of that seen in the frontal and temporal cortices in human brain. In the rat brain, the expression level of tau with three microtubule-binding repeats (3R-tau) was comparable in the hippocampus, entorhinal cortex, frontal cortex, parietal-temporal cortex, occipital-temporal cortex, striatum, thalamus, olfactory bulb and cerebellum. However, the expression level of 4R-tau was the highest in the entorhinal cortex and the lowest in the cerebellum. Tau phosphatases, kinases, microtubule-related proteins, and other tau pathology-related proteins were also expressed in a region-specific manner in the rat brain. These results suggest that higher levels of tau and tau kinases in the entorhinal cortex and low levels of these proteins in the cerebellum may accounts for the vulnerability and resistance of these representative brain regions to the development of tau pathology, respectively. The present study provides the regional expression profiles of tau and tau pathology-related proteins in the brain, which may help understand the brain regional vulnerability to tau pathology in neurodegenerative tauopathies.